The influence of the ultrasonic field on the efficiency of leachate treatment in the SBR reactor - Monika Gałwa-Widera (Desalination and Water Treatment)
The aim of the study was to investigate the effectiveness of ultrasonic disintegration of landfill leachates in a sequential batch reactor (SBR). The study was conducted in two stages, with the first stage consisting of determining the most favorable sonication conditions, include vIntime and amplitude. The second stage focused on leachate treatment in SBR with the participation of sonicated and unsonicated landfill leachates. The effectiveness of the treatment process was determined based on the removal rate of selected parameters: chemical oxygen demand (COD), total organic carbon (TOC), inorganic carbon (IC), ammonium nitrogen (N-NH4), total nitrogen (TN), and the course of pH changes. The study showed that sonication increases biodegradability and reduces their toxicity. The use of pre-sonication before biological treatment improved the degree of removal of the tested parameters by about 10 %. The use of an ultrasonic field allows for the implementation of the treatment process. Moreover, it was found that in order to increase the efficiency of wastewater treatment, the individual phases in the SBR and the pollutant load should be optimize.